(untitled) (Polifonia, 1995)
ABSTRACT: Based on a discourse methodological perspective, this study analyzes the narrative "No tempo em que só a namorada podia falar errado" ("In the time that only the girlfriend could make grammatical mistakes") by Augusto Nunes. This author correlates the situational conditions of the text production and the formal modes of discourse to question the author’s viewpoint that attempts to disqualify Luiz Inácio Lula da Silva for the possition of president of Brazil.